Familial Mediterranean fever presenting as fever of unknown origin in Korea - Jun Hee Lee (Korean Journal of Pediatrics, 2016)
Familial Mediterranean fever (FMF) is the most common Mendelian autoinflammatory disease, characterized by uncontrolled activation of the innate immune system that manifests as recurrent brief fever and polyserositis (e.g., peritonitis, pleuritic, and arthritis). FMF is caused by autosomal recessive mutations of the Mediterranean fever gene, MEFV which encodes the pyrin protein. Although FMF predominantly affects people from Mediterranean and Middle Eastern ethnic origins, 3 cases of FMF have been reported in Korea since 2012. We report another case of FMF in Korea in which the patient presented with a month-long fever without serositis. After treatment with colchicine was initiated, the patient’s symptoms quickly subsided. The response to colchicine was helpful for diagnosis. We compare the FMF genotypes in Korea with in other countries. Studying FMF cases in Korea will help establish the best MEFV exons to use for screening and diagnosis of Korean FMF.